PERJANJIAN BAKU YANG MEMUAT KLAUSULA EKSONERASI DALAM PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN - Shinta Rachmaniyah; Dipo Wahyoeno (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The birth of a standard agreement containing an exoneration clause basically intends to provide easier and more practical access for the parties who will enter into an agreement. The prohibition on using the transfer of responsibility clause can be seen in the rule of law in Indonesia, which is located in Article 18 of Law no. 8 of 1999 concerning Consumer Protection. In this case, the issue raised is how the exoneration clause applies in the standard agreement from the point of view of consumer protection law. In this study, the research method used by the author is a normative legal research method that uses a statutory approach or the so-called statute approach, a conceptual approach or the so-called conceptual approach and views according to experts. The results of the study show that the Standard Agreement which contains an exoneration clause can create legal consequences for consumers, namely the obligations that should be borne by the seller or business actor are the obligations of the buyer or consumer. UUPK or Law no. 8 of 1999 concerning Consumer Protection requires sellers or business actors to immediately match the standard agreement used for the provisions of the law, but in implementation this is difficult to enforce. Procedures and prohibitions regarding the application of standard agreements are planned to occupy the position of the buyer or consumer commensurate with the seller or business actor in accordance with the principle of freedom of contract and also prevent the emergence of actions that can later be detrimental to the buyer or consumer due to the lack of understanding, the buyer or consumer is exploited by the perpetrator. effort and also an equal position between the two parties. If the seller or business actor has set a standard clause that is prohibited in the agreement, the legal consequences of the standard clause are declared null and void.